His-bundle pacing in CHF-patients with narrow QRS and chronic AF – an upgrade from single-chamber to dual-chamber ICD. (25th November 2020) - Ciesielski, A; Slawuta, A; Zabek, A; Boczar, K; Malecka, B; Hiczkiewicz, J; Gajek, J
Abstract: : A single-chamber ICD is a standard method for primary SCD prophylaxis. In patients with chronic atrial fibrillation it does not contribute to the regularization of heart rate, which is crucial for proper treatment. Moreover, to avoid the deleterious effect of right ventricular pacing only minority of the patients with single chamber ICD get the appropriate, recommended dose of beta-blockers. The aim of our study was to assess the efficacy of direct His-bundle pacing in a population of patients with congestive heart failure and chronic atrial fibrillation using upgrade from single chamber to dual-chamber ICD and atrial channel to perform the His-bundle pacing Methods: The study population included 39 patients (37 men, 2 women) aged 67.2±9.3 years, with CHF and chronic AF implanted primarily with single chamber ICD with established pharmacotherapy and stable clinical status. Results: The echocardiography measurements at baseline and during follow-up were presented in the table: During short period (3–6 months) of follow-up the mean values of EF and LV dimensions significantly improved. This was also accompanied by functional status improvement. Conclusions: His-bundle-based pacing in CHF-chronic AF patients contributes to significant echocardiographic and clinical improvement. Standard single-chamber ICD implantation in CHF-chronic AF patients yields only SCD prevention without influence on remodeling process. The physiological pacing contributes to better pharmacotherapy. Funding Acknowledgement: Type of funding source: None